Kinematic analysis of a new 5-DOF modular parallel robot for brachytherapy. (February 2015) - Plitea, Nicolae; Szilaghyi, Andras; Pisla, Doina
Abstract: Cancer represents one of the main causes of the death. Huge efforts have been made by the scientific community to provide better cancer treatment solutions. An innovative option is the brachytherapy (BT), a local radiation technique for cancer treatment, which enables the delivery of high doses of radiation inside the tumors. BT usage is limited by the insufficient accuracy of the radioactive seeds placement. In order to eliminate these limitations, the authors propose an innovative modular structure which would enable the precise positioning of the BT needles in any part of the patient body. The paper presents the kinematic modeling of the new 5-DOF robotic structure. The workspace analysis and the singularities are studied and the dexterous workspace for a given insertion point inside the patient is also shown. Finally, some numerical simulations of different BT needle trajectories are included. Highlights: A new 5-DOF modular parallel robotic structure for brachytherapy is presented. The geometric and kinematics models of the new parallel structure are illustrated. The robot workspace is computed and illustrated following the singularities analysis. Simulation and numerical results of the kinematics models are obtained.